Laboratory decay resistance of palmyra palm wood - Li, Xiaoping; Leavengood, Scott; Cappellazzi, Jed; J. Morrell, Jeffrey (Maderas. Ciencia y Tecnología, 2018)
The decay resistance of palmyra palm wood[1] (Borassus flabellifer), also referred to as sugar palm, was assessed in laboratory soil block tests against Oligoporus placenta, Gloeophyllum trabeum, Irpex lacteus, and Trametes versicolor as well as in a non-sterile soil burial test designed to encourage soft rot attack. Mass losses on pine control blocks were consistent with aggressive decay conditions for all but those exposed to Irpex lacteus, while mass losses for palm wood blocks exposed to the same fungi ranged from 0.46% to 10.6%. The magnitude of mass losses would categorize palm wood as resistant to highly decay resistant, suggesting that these materials might perform well in exterior above ground applications. Mass losses were weakly correlated with density suggesting that selection of denser wood will result in better performing materials in these applications. Field tests to confirm these results are encouraged.